Books from Sofia library in the cyrillic book collection at the Russian state library - Oleg Khromov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article tires to identify early printed editions from Novgorod churches and monasteries as part of the Russian State Library (RSL) collection. It shows the way they got to the RSL and provides a method for their attribution. In the XVIII century, the books were collected in the St. Sophia Cathedral library in Novgorod. In the middle of the XIX century, some of them were brought to the library of the St. Petersburg Theological Academy. In the 1870s, the idea of exchanging book duplicates between the St. Petersburg Theological Academy and the Moscow Public and Rumyantsev’s Museums arose. It was supported by His Eminence Metropolitan of St. Petersburg, Novgorod and Finland Isidore. In 1874, the Rumyantsev’s Museum received 126 books. Among them, there were books from the Kirillo-Belozersk Monastery, the Sofia Library and some items of an unknown origin (without owner's signs). The article shows the methodology and process of attribution the books from Novgorod monasteries and churches based on the study of owners’ signs (for example, dedicatory inscriptions, authographs and other notes) taking in account the history of the Sofia Library collection. There were some contributions from the nobility, for example, D. M. Bashmakov, a statesman of the 17th century; or Princess Natalia Kirillovna, a mother of Peter I, who made a donation to the Novgorod Convent of Great martyr Euphemia the Glorious. This fact allows us to look at the history of monastic libraries in a more detailed way exploring their parts. The attribution of the books of Novgorod origin at the RSL collection illustrates the research method for regional Cyrillic book collections, which for the most part remains unexplored. Keywords: the early Cyrillic printed books, the Sofia Library, Novgorod Books, editions of the Moscow Printing House, the history of libraries, St. Petersburg Theological Academy, monastic and church libraries, books of Ancient Russia, regional collections of old printed books.